A case report of Management of impaction colic in Donkey in Ibadan, Nigeria (2020)
A 13 year old male donkey (jack), weighing 171 kg was presented with history' of frequent prolonged recumbency and eliciting sand bath action. The donkey was dehydrated, anorexic, inactive, refused to drink and no defecation. Rolling, bloating, uneasiness, distress were also observed, grunting sound was also heard whenever the animal attempted to rise from recumbency. Rectal temperature was 36.6°C, pulse and respiratory rates were 60 and 30 per minute, respectively. Mucous membrane initially appeared normal but later became congested with generalised bruises on the body of the donkey especially at the bony prominences. Colic was clinically diagnosed and treatment immediately instituted. Animal was drenched with 1 litre of liquid paraffin; 2 litres of lactated Ringer’s solution was given intravenously, I/V; lntramuscular(l/M) injections of 8 mis (2.25mg/Kg) of vitamin B complex and 3.8 mis of50mg/ml (1.1 mg/Kg) Flunixin Meglumine were also administered. The patient was treated for five consecutive days with significant improvement on the third day. The rolling, bloating, distress and uneasiness were relieved after day four of treatment and the donkey was discharged on the fifth day. This report highlighted the causes, type and nature of this particular case, management procedures and preventives strategy of colic in donkey.